Avaliação funcional e morfológica do músculo estriado esquelético e junções neuromusculares em ratos submetidos a um modelo de paralisia cerebral - Buratti, Pâmela (2017)
Cerebral palsy (CP) corresponds to a motor disorder, caused by non-progressive injury in the immature brain, resulting in changes in muscle tone, movement and postureThis study aimed to investigate the morphofunctional characteristics of the plantar muscle in an animal model of CP. To obtain the litters were used for paired adult Wistar rats (11 females and 06 males). The pregnant females were separated in: rats injected intraperitoneally with vehicle (100 μL of sterile saline) and rats injected intraperitoneally with lipopolysaccharide (LPS; 200 μg / kg LPS in 100 μL sterile saline). The injections were performed every 12 hours, from the 17th gestational day until the end of gestation (21st gestational Day). The male offspring were separated in: Control group (CG, n = 8) - pups of rats injected with saline solution during pregnancy, and CP group (CPG, n = 8) - pups of rats injected with LPS during pregnancy, submitted to perinatal anoxia and sensorimotor restriction. For perinatal anoxia, the pups were placed in a closed chamber, partially immersed in water at 37 °C ± 1, with a flow of 9 L/min of nitrogen (100%) for 20 minutes on the day of birth (postnatal day 0, P0). From the 1st to the 30th postnatal day (P1 to P30), the CPG animals were submitted to sensorimotor restriction for 16 hours/day. At 29 and 45 days of age, the animals were evaluated in the open-field test, being collected time of displacement, crossing, rearing and grooming frequency. At the 48th postnatal day the animals were weighed and the collection, measurement of weight and muscle length were performed. The muscle fibers were evaluated in histological sections submitted to Hematoxylin-Eosin (HE), NADH-TR reaction (Nicotinamide Adenine Dinucleotide - Tetrazolium Redutase) and transmission electron microscopy; intramuscular collagen was studied with Masson's trichrome staining; and the neuromuscular junctions (NMJs) ascertained by the Nonspecific Esterase reaction. The data were statistically evaluated using the parametric Student t-test and the non-parametric Mann-Whitney test, according to the Kolmogorov-Smirnov normality test.It was verified that when compared to CG the CPG presented: reduction in time of displacement, number of crosses and rearing at 29 days of age; in the time of displacement and rearing at 45 days of age; of body parameters (body weight, weight and length soleus muscle); of the nuclei/fiber and capillary/fiber relations; increased percentage of collagen; reduction of cross-sectional area of muscle fibers type I; increased counts of fibers type I; in the number of myofibrillar disorganization, of the Z line and dissolution of the Z line; and reduction in area, larger and smaller diameters of NMJs. It is concluded that the PC model used altered the morphological characteristics of the skeletal striated muscle, causing deficits in the locomotor activity of the animals, as evidenced by the results of the evaluation in the open field.